Viscosity and stickiness of dental resin composites at elevated temperatures - Loumprinis, Nikolaos; Maier, Eva; Belli, Renan; Petschelt, Anselm; Eliades, George; Lohbauer, Ulrich (Dental Materials, 2021)
Objective: To investigate the influence of pre-heating different classes of dental resin composites on viscosity and stickiness at five different temperatures. Methods: Six flowable, five conventional packable, and one thermo-viscous bulk-fill resin composites were heated up to 54 °C in a plate-plate rheometer to determine their complex viscosity. Normal force measurements were carried out for the six packable materials to determine the unplugging force and unplugging work (stickiness) over the same temperature range. Data were analyzed using Kolmogorov–Smirnoff test, one-way ANOVA and Tukey Post Hoc test with α = 0.05 as level of significance. Results: At 23 °C packable composites showed viscosity between 6.75 and 19.14 kPa s, while flowable composites presented significantly lower viscosities between 1.31 and 2.20 kPa s. Pre-heating led to a drop of 30–82% in the viscosity of packable materials. The thermo-viscous material dropped to the level of flowables at 45 and 54 °C thus behaving as a packable composite at room temperature with flowable-like viscosity at higher temperatures. No statistically significant differences for viscosity were observed among flowable composites at any temperature. The unplugging force decreased for packable composites, while their unplugging work generally increased at elevated temperature. At 23 °C unplugging force was measured between 7.50 and 19.18 N, while pre-heating up to 54 °C led to values between 2.9 and 6.2 N. Regarding unplugging work at 23 °C the calculated values were between 3.0 and 8.9 × 10−3 J and at 54 °C between 8.8 and 13.0 × 10−3 J. Significance: Pre-heating significantly reduced viscosity of highly viscous resin composites, while no influence was shown for flowable composites. In general stickiness, measured as unplugging work, increased at elevated temperatures. The thermo-viscous material showed low viscosity comparable to flowable composites at 45 and 54 °C, yet its stickiness did not increase significantly compared to the values at 23 °C.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Activation energy; Handling properties; Pre-heating; Resin composite; Rheology; Stickiness; Temperature; Viscosity